Features of the Hydrological Regime of the Chaika Lake System, Assessment of Water Quality and Bottom Sediments - Istomin Aleksandr; Mezhevova Alina; Istomin Sergey; Khrenov Igor (Russian Journal of Earth Sciences)
An assessment of the state of aquatic ecosystems in the northern (“high”) part of the Volga-Akhtuba floodplain was carried out (using the Peschany erikk of the Chaika lake system as an example). Based on the results of monitoring in 2021–2023, the current hydrological regime of the Chaika lake system was studied, recommendations were prepared to prevent the degradation of water bodies included in the system. The effectiveness of measures to clear floodplain reservoirs and build regulating culverts was recorded. Monitoring of the passage of spring floods in the Chaika lake system, located on the territory of the Volga-Akhtuba floodplain, was carried out. A dependence was revealed between the direction of water movement through the reservoirs of the lake system depending on the discharge through the Volgograd hydroelectric power station and the water content of the reservoirs of the Kashirinsky and Krasnoslobodsky water conduits. Recommendations have been prepared for the management of regulating water-passing structures for the purpose of efficient irrigation of the Chaika lake system, taking into account the hydrological regime of the Krasnoslobodsk and Kashirinsky watercourses. Retrospective interpretation of Landsat-5, Landsat-7 and Sentinel-2 space images was conducted, as a result of which a degraded lake was identified and recommendations for its restoration were proposed. Comprehensive studies of water and bottom sediments were conducted, including for pollution by heavy metals and pesticides. It was revealed that the concentration of some studied elements exceeds the standard or is close to exceeding it. Recommendations are given for further monitoring of the state of water bodies of the Chaika lake system, as well as a possible option for using bottom sediments.